Meningkatkan Strategi Pemasaran di Desa Sindangprabu - Purnamasari, Ismi; Nurfadillah, Rifa Sri; Hamidah, Sabrina; Oktavia, Yayu; Fajar, Hanafi Arya; Muttaqin, Dadan Ahmad Badar; Maulidiyana, Maya; Ulumudin, Jamil; Nurani, Pelita Maulida; Taufik, Risman; Akihari, Bobby Dwitama Eden; Fazri, Muhammad Insan Kamil; Agriyanto, Ari; Zulkarnaen, Ade Iskandar; Latif, Abdul; Najib, Rafi; Fauzi, Khasbi Aqsal; Nurhayati, Mila; Agistina, Aini; Prasetya, Yoga Budi; Alamsyah, Restu (Institut Teknologi Garut, 2023)
The development of the business in Sindang Prabu Village really encourages us to deepen more on how to improve the marketing strategy of businesses owned by local residents in the neighborhood. The Sindang Prabu village area has many resources that can be used to improve small businesses, especially in marketing. The purpose of this research itself is to explain how a good marketing strategy can increase the level of sales of products owned by entrepreneurs. The method used in this research is qualitative method. The sample used in this study is a micro business owned by local residents. The functions and materials used in this research study are intended to find out how to do or a good marketing strategy in order to increase sales of micro-entrepreneurs' products. The results of the analysis from conducting a survey directly show that the lack of promotion carried out by business owners makes the marketing value unsatisfactory of the product and also the constraints on the lack of auxiliary tools such as machines in the production process become a significant influence in the marketing process carried out by business owners , it can be seen that promotions and also tools in the production process can be the right solution in increasing the marketing of products owned by these micro entrepreneurs.